Challenges and Opportunities to Updating Prescribing Information for Longstanding Oncology Drugs. (8th December 2019) - Balogh, Erin P.; Bindman, Andrew B.; Eckhardt, S. Gail; Halabi, Susan; Harvey, R. Donald; Jaiyesimi, Ishmael; Miksad, Rebecca; Moses, Harold L.; Nass, Sharyl J.; Schilsky, Richard L.; Sun, Steven; Torrente, Josephine M.; et al.
Abstract: A number of important drugs used to treat cancer—many of which serve as the backbone of modern chemotherapy regimens—have outdated prescribing information in their drug labeling. The Food and Drug Administration is undertaking a pilot project to develop a process and criteria for updating prescribing information for longstanding oncology drugs, based on the breadth of knowledge the cancer community has accumulated with the use of these drugs over time. This article highlights a number of considerations for labeling updates, including selecting priorities for updating; data sources and evidentiary criteria; as well as the risks, challenges, and opportunities for iterative review to ensure prescribing information for oncology drugs remains relevant to current clinical practice. Abstract : The U.S. Food and Drug Administration is undertaking a pilot project to develop a process and criteria for updating prescribing information for long‐standing oncology drugs. This article highlights a number of considerations for labeling updates.